2008
DOI: 10.1007/s00403-008-0904-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of interferon-gamma and tumor necrosis factor alpha polymorphisms with susceptibility to vitiligo in Iranian patients

Abstract: Vitiligo is a common skin disorder that is caused by selective destruction of melanocytes, resulting in disfiguring loss of pigment. There are convincing evidences that cytokines and T cell mediated immunity may have a role in its pathogenesis. Given the fact that cytokine production is under genetic control, in this study, we have investigated IFN-gamma +874 T/A and TNF-alpha -308 G/A gene polymorphisms in a total of 176 vitiligo patients and 545 controls. IFN-gamma +874 T/A and TNF-alpha -308 G/A gene polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 32 publications
5
41
0
Order By: Relevance
“…A similar association between the TNF-α -308 (G/A) polymorphism and vitiligo was recently reported in Iranian patients (Namian et al, 2009). Contrary to these reports, Yazici et al (2006) found no association between TNF-α -308 promoter polymorphism and vitiligo in Turkish patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A similar association between the TNF-α -308 (G/A) polymorphism and vitiligo was recently reported in Iranian patients (Namian et al, 2009). Contrary to these reports, Yazici et al (2006) found no association between TNF-α -308 promoter polymorphism and vitiligo in Turkish patients.…”
Section: Discussionsupporting
confidence: 82%
“…Linkage and association studies have also provided strong evidence for the presence of multiple vitiligo susceptibility genes on different chromosomes. Different candidate genes for vitiligo have been identified among different populations (Gavalas et al, 2006;Shajil et al, 2006;Namian et al, 2009;Alkhateeb and Qarqaz, 2010;Spritz, 2012;Karaca et al, 2013). Our earlier study showed a significant association between HLA-DRB4* 010101 and HLA-B7, -B15, -Bw6, -Cw6, and -Cw7 and vitiligo in Saudi patients (Abanmi et al, 2006), suggesting that various genetic factors operate simultaneously in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Three were excluded because no extractable genotype data or family data were included. Thus, 15 studies met our inclusion criteria (Brinkman et al, 1997;Vinasco et al, 1997;van Krugten et al, 1999;Yen et al, 2001;Fabris et al, 2002;Zwiers et al, 2004;Correa et al, 2005;Rodríguez-Carreón et al, 2005;Yazici et al, 2006;Namian et al, 2009;Emonts et al, 2011;Laddha et al, 2012;Salinas-Santander et al, 2012;Al-Harthi et al, 2013;You et al, 2013). Ten studies examined RA and 5 examined vitiligo.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…The most common polymorphism occurs at position -308 (TNF-α-308G/A), which may affect the cytokine production (Wilson et al, 1997;Louis et al, 1998;Abraham and Kroeger, 1999). A number of case-control studies have been conducted to investigate the association between the TNF-α-308G/A polymorphism and vitiligo risk (Yazici et al, 2006;Namian et al, 2009;Laddha et al, 2012;Salinas-Santander et al, 2012;Al-Harthi et al, 2013;Aydingoz et al, 2015). However, the results of these studies have been inconsistent, which may be attributed to small sample sizes and the differences in ethnic populations.…”
Section: Introductionmentioning
confidence: 98%